PERUBAHAN SOSIAL (SOSIAL CHANGE) DALAM PENDIDIKAN AGAMA ISLAM - Khotimatus Sholihah (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
Education and social change, both are interrelated with each other. Both influence each other, so that it has a wide impact in society. The link between education and social change is the occurrence of changes in the structure and function of the social system, which includes education, because education exists in society, be it formal, informal or non-formal education. The speed of technological development is one of the causes of social change experienced by society. The changes that are so visible are the problems of morals, morals, and human behavior that are increasingly varied in social interaction. This makes the position of Islamic religious education very important. Islamic education aims to achieve balanced growth in the child in his personality as a total human being through spiritual practice, rational intelligence, feelings and the five senses. Therefore, education should be a service for human growth (students) in all aspects of spiritual, intellectual, imagination, physical, scientific, linguistic, both individually and collectively and motivate all these aspects towards goodness and the achievement of perfection. Education must be able to answer all the problems experienced by society by updating all the roles and functions of education, such as the function of education as social change, the function of transferring cultural values ​​(cultural transformation), the function of developing and strengthening social relations.